2022
DOI: 10.1186/s12935-022-02560-8
|View full text |Cite
|
Sign up to set email alerts
|

LINC01806 mediated by STAT1 promotes cell proliferation, migration, invasion, and stemness in non-small cell lung cancer through Notch signaling by miR-4428/NOTCH2 axis

Abstract: Background Non-small cell lung cancer (NSCLC), the most primary lung cancer subtype, threatens human health globally. Long non-coding RNAs (lncRNAs) have been uncovered to affect multiple cancers progression. Nevertheless, the specific function of long intergenic non-protein coding RNA 1806 (LINC01806) in NSCLC remains elusive. Methods RT-qPCR and western blot were involved in this study. The influence of LINC01806 on NSCLC was assessed by in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Despite the results generated from most studies supporting the antineoplastic effect of STAT1, 36 accumulating evidence suggests that STAT1 also exerts a tumor-promoting function. [42][43][44] In some malignant phenotypes, STAT1 can act as an oncoprotein or tumor suppressor in the same cell type, depending on the specific genetic background. 45,46 In this present study, we found that STAT1 was highly expressed in MPN-derived leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the results generated from most studies supporting the antineoplastic effect of STAT1, 36 accumulating evidence suggests that STAT1 also exerts a tumor-promoting function. [42][43][44] In some malignant phenotypes, STAT1 can act as an oncoprotein or tumor suppressor in the same cell type, depending on the specific genetic background. 45,46 In this present study, we found that STAT1 was highly expressed in MPN-derived leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…There was an evident regression of the tumors developed from LINC01806-silenced NSCLC cells. However, acceleration in tumor growth was noted when NSCLC cells were co-transfected with miR-4428 antagomirs or overexpression of NOTCH2 [ 17 ].…”
Section: Transcriptional Regulation Of Oncogenic Lncrnas By Stat1mentioning
confidence: 99%
“…Since the discovery of PHLPPs, a lot of studies have been conducted on illuminating of its substrates, including STAT1, MST1, S6K1 and so on (24,68,69). Although these substrates were associated with the development of lung cancer (70)(71)(72), there was no direct evidence that they were associated with PHLPPs in LC. In addition, in a global PHLPP knocked out (PHLPP -/-) mouse model, researcher has focused more on the gastrointestinal tract, including the progress of cancer and the changes of immune cells in the immune microenvironment.…”
Section: Xia Et Almentioning
confidence: 99%